2014
DOI: 10.1039/c4cp03252g
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved water dimer spectra in atmospheric air and pure water vapour in the 188–258 GHz range

Abstract: New experimental results regarding "warm" water dimer spectra under equilibrium conditions are presented. An almost equidistant series of six peaks corresponding to the merged individual lines of the bound dimer with consecutive rotational quantum numbers is studied in the 188-258 GHz frequency range in water vapour over a broad range of pressures and temperatures relevant to the Earth's atmosphere. The series is a continuation of the sequence detected earlier at lower frequencies at room temperature. The sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 51 publications
2
16
0
6
Order By: Relevance
“…Finally, recent laboratory studies have resulted in unambiguous detection of H 2 O dimer absorption in the millimeterwave range (Tretyakov et al, 2013;Serov et al, 2014) and to the development of a model to describe it . This absorption shows spectral variation on scales that are not accounted for in the current version of MT_CKD or in Liebe-based models.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…Finally, recent laboratory studies have resulted in unambiguous detection of H 2 O dimer absorption in the millimeterwave range (Tretyakov et al, 2013;Serov et al, 2014) and to the development of a model to describe it . This absorption shows spectral variation on scales that are not accounted for in the current version of MT_CKD or in Liebe-based models.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…Line parameters (line position and strength, the airbroadened half-width, the self-broadened half-width, the temperature exponent of the width and the pressure shift) may be obtained from laboratory experiments or from theoretical calculations and are collected in databases such as the widely used the high-resolution transmission compilation (HITRAN, Rothman et al, 2013). The current edition of HITRAN provides the parameters for Voigt profiles, but future editions of the database will allow for inclusion of additional parameters for more sophisticated line shape models (Tennyson et al, 2014). Sensitivity tests on Voigt parameters, performed using MonoRTM, have shown that illustrative uncertainties on the foreign (±3 %) and self-broadened (±15 %) half widths, on the temperature exponent (maximum of 15 %) and the pressure shift (maximum of 20 %) are certainly too small to explain the observed bias (Payne et al, 2008), and the spectroscopic community (lab and modellers) believes that the accuracy of these parameters is higher than the above numbers.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…Âåëè÷èíà s eq K (400 Ê) = = 0,003 àòì -1 ïðèìåðíî â 2 ðàçà íèaeå, ÷åì ïîëó÷åííàÿ èç àb initio ðàñ÷åòîâ â ðàáîòå [12] (0,0063 àòì -1 ). Ýòîò ôàêò, îäíàêî, õîðîøî ñîãëàñóåòñÿ ñ ðåçóëüòàòîì âîññòàíîâëåíèÿ ñîäåðaeàíèÿ ñ-äèìåðîâ â [13] íà óðîâíå 0,65 îò çíà÷åíèé Scribano et al [12] èç ýêñïåðèìåíòàëüíûõ ñïåêòðîâ ïîãëîùåíèÿ âîäÿíîãî ïàðà â ãèãàãåðöîâîé îáëàñòè ñïåêòðà. Çíà÷åíèå ïîëíîé êîíñòàíòû äèìåðèçàöèè, ïîëó÷åííîé èç ïîäãîíêè ê ñïåêòðó êîíòèíóóìà ïðè 400 Ê, ñîñòàâèëî s m eq eq K K + = 0,028 àòì -1 , îíî ïðèìåðíî â 2 ðàçà ïðåâûøàåò âåëè÷èíó, ïîëó÷åííóþ èç àb initio ðàñ÷åòîâ [13], êîòîðàÿ ñîñòàâëÿåò ∼ 0,013 àòì -1 .…”
Section: ðåçóëüòàòû è îáñóAeäåíèåunclassified
“…Ýòîò ôàêò, îäíàêî, õîðîøî ñîãëàñóåòñÿ ñ ðåçóëüòàòîì âîññòàíîâëåíèÿ ñîäåðaeàíèÿ ñ-äèìåðîâ â [13] íà óðîâíå 0,65 îò çíà÷åíèé Scribano et al [12] èç ýêñïåðèìåíòàëüíûõ ñïåêòðîâ ïîãëîùåíèÿ âîäÿíîãî ïàðà â ãèãàãåðöîâîé îáëàñòè ñïåêòðà. Çíà÷åíèå ïîëíîé êîíñòàíòû äèìåðèçàöèè, ïîëó÷åííîé èç ïîäãîíêè ê ñïåêòðó êîíòèíóóìà ïðè 400 Ê, ñîñòàâèëî s m eq eq K K + = 0,028 àòì -1 , îíî ïðèìåðíî â 2 ðàçà ïðåâûøàåò âåëè÷èíó, ïîëó÷åííóþ èç àb initio ðàñ÷åòîâ [13], êîòîðàÿ ñîñòàâëÿåò ∼ 0,013 àòì -1 . Ýòî ìîaeåò ñâèäåòåëüñòâîâàòü ëèáî î íå âïîëíå òî÷íîé îöåíêå äîëè ì-äèìåðîâ èç âòîðîãî âèðèàëüíîãî êîýôôèöèåíòà [13], ëèáî î âêëàäå êàêîãî-òî äîïîëíèòåëüíîãî (èíîãî, ÷åì äèìåðû) ìåõàíèçìà â êîíòèíóàëüíîå ïîãëîùåíèå â ðàññìîòðåííûõ íàìè ïîëîñàõ.…”
Section: ðåçóëüòàòû è îáñóAeäåíèåunclassified